O16 Enteral autonomy and central line sepsis in Home Parenteral Nutrition (HPN) patients discharged since 2015; single centre experience. (12th September 2022) - Bache, Emma; Hutchison, Lizzie; Dinning, Ali; Phipps, Amy; Broad, Sam; Thorpe, Matt; Tozer, Richard; Greene, Hazel; Knight, Christopher; Wiskin, Tony
Abstract : Background: For a patient and their family, preparing to be discharged home with parenteral nutrition (PN) can be a daunting experience. Considerable time is spent educating parents over care of the central venous catheter in order to prevent infection as this is an important factor in HPN outcomes. Unfortunately, there are very few modern cohorts detailing outcome of HPN to enable adequate counselling and support for families. The aim of the study was to collate and analyse outcomes of paediatric patients discharged on home PN, most notably rates of line sepsis and enteral autonomy (no longer requiring PN). Methods: Patients discharged on Home PN by our centre from 1/1/2015 to 31/12/2020 were included. Data were censored at 30/09/2021. Children on home PN prior to 2015 were excluded. Medical records and laboratory results were reviewed in Bristol and in the local hospital of each patient. Data collected included indication for home PN, numbers of days of home PN per year, episodes of line sepsis per year (blood culture positive infection or line associated infection that necessitated line removal) and line sepsis rate defined as the number of episodes of line sepsis per 1000 days of home PN. Results: Overall 30 patients met the inclusion criteria and were included in the study. Indications for home PN were short bowel syndrome (19), dysmotility (4), functional gastrointestinal disorders (1), fabricated/induced illness (1), enteropathy (2) and other (3). Of the 19 children with Short Bowel Syndrome, 11 achieved enteral autonomy receiving a median of 448 days HPN (range 23 – 1379 days); 3 of these patients were over 3 years of age before they achieved enteral autonomy. Three other children achieved enteral autonomy including 1 child with FII and 2 children defined as 'other': 1 of these had frozen abdomen post-surgery, 1 was a child born with gastroschisis. Two children transferred to other services still requiring HPN; 1 teenager transitioned to adult services having received 1750 days of PN; 1 child with short bowel syndrome was transferred to another unit following family relocation. 14 of the 30 children continue to receive HPN in our service, these include the 2 children with enteropathy, 4 children with dysmotility, and 7 children with short bowel syndrome. For these 7 children with short bowel syndrome; median PN duration was 1666 days, (range 121 – 2157 days); four children are school age and all four attend mainstream school. From 2015 a nutrition support team was established with dedicated consultant, nurse specialist and dietetic time. The team introduced a wide range of interventions to reduce line sepsis including education of hospital staff and carers, line care devices and sepsis plans. Overall there were 1.11 line sepsis episodes per 1000 line days. Line sepsis rate per year is shown in the figure 1 . Conclusions: Enteral autonomy for children with short bowel syndrome in our centre is comparable to data from larger cohorts. The intervention of a dedicated nutrition support team has had a dramatic impact on reducing rates of central line infection.